2020
DOI: 10.1002/sres.2706
|View full text |Cite
|
Sign up to set email alerts
|

A paradigm of safety management in Industry 4.0

Abstract: Safety management determines and implements safety policy. It is closely intertwined with industrial development. As the Fourth Industrial Revolution, Industry 4.0 presents new challenges and opportunities for safety management. The paper identifies three stages, namely, Safety 1.0, Safety 2.0 and Safety 3.0, for the evolution of safety management by considering safety principles, technologies and modes. A theoretical framework that integrates Safety 3.0 and Industry 4.0 is presented. Furthermore, knowledge gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(21 citation statements)
references
References 80 publications
1
20
0
Order By: Relevance
“…As highlighted by Hollingsworth (2020), sites may be monitored directly via web or security cameras or by drones on larger sites. While the results confirm past studies where construction has been reported to be slow to adopt technology to enhance H&S (Liu et al, 2020;Nnaji et al, 2020), they also highlighted a chasm in the delivery chain of H&S during the COVID-19 pandemic. Also, inadequate site re-design to conform to COVID-19 pandemic H&S requirements affects the ability to physically/socially distance and avoid direct contact among co-workers.…”
Section: Factor Analysissupporting
confidence: 86%
“…As highlighted by Hollingsworth (2020), sites may be monitored directly via web or security cameras or by drones on larger sites. While the results confirm past studies where construction has been reported to be slow to adopt technology to enhance H&S (Liu et al, 2020;Nnaji et al, 2020), they also highlighted a chasm in the delivery chain of H&S during the COVID-19 pandemic. Also, inadequate site re-design to conform to COVID-19 pandemic H&S requirements affects the ability to physically/socially distance and avoid direct contact among co-workers.…”
Section: Factor Analysissupporting
confidence: 86%
“…Example(s): User-friendly interfaces, such as rotary controls and instructional displays, are an upcoming topic of notable significance to the further development of the manufacturing system (I4, I8). Governance of data, product security & liability A company’s ability to prepare, prevent, recover, and learn from actual or potential cyber security threats (Babiceanu & Seker, 2016 ; Liu et al, 2020 ; Schuh et al, 2020 ; Weber et al, 2019 ). Explanation: Due to the implementation of connected products and the associated data exchange within and across organisational boundaries, the protection of intellectual property plays an essential role, as does the protection of customer and employee data from threats such as cyber-attacks, unauthorised access, and industrial espionage (Liu et al, 2020 ; Schuh et al, 2020 ).…”
Section: Information Systems Capability Framework For Industry 40mentioning
confidence: 99%
“… Governance of data, product security & liability A company’s ability to prepare, prevent, recover, and learn from actual or potential cyber security threats (Babiceanu & Seker, 2016 ; Liu et al, 2020 ; Schuh et al, 2020 ; Weber et al, 2019 ). Explanation: Due to the implementation of connected products and the associated data exchange within and across organisational boundaries, the protection of intellectual property plays an essential role, as does the protection of customer and employee data from threats such as cyber-attacks, unauthorised access, and industrial espionage (Liu et al, 2020 ; Schuh et al, 2020 ). From an ex-ante perspective, the ‘prepare and prevent’ strategy provides a comprehensive analysis of the present threat situation and the implementation of security measures that cover product administration and data ownership structures as user authentication mechanisms.…”
Section: Information Systems Capability Framework For Industry 40mentioning
confidence: 99%
“…Smart factory (SF) is a highly flexible and intelligent factory where humans, machines, sources and products communicate just like a social network. SF is able to react and respond to changing customer requirements almost instantly (Liu et al , 2020). Because, in a production environment where there are rapid changes, the AR system has brought a revolution.…”
Section: Contributions Of Augmented Realitymentioning
confidence: 99%